Intellectual Ability Effect on Management Lecturer Performance: The Role of Competence as Position Improvement - Mochammad Munir Rachman; Bisma Irianto; Sugijanto Sugijanto (APMBA (Asia Pacific Management and Business Application), 2022)
Within the Indonesian higher education context, the tri dharma (three main academic activities) of lecturer activities are ensured to improve their performance. It is related to their intellectual ability, and competence. Both of these are important factors in supporting the quality of higher education. The study was conducted on 200 respondents by distributing questionnaires to the respondents. This paper finds that intellectual ability has a strong influence on the competence of lecturers, indirectly being able to produce a positive effect on their performance. However, it is not as strong as directly affecting their performance. This is realized, they have a logical, inspirational, creative and innovative thinking pattern in completing the tri dharma task. Such as education, producing scientific papers published in reputable national and international journals, publishing the results of community service, and contributing to other activities. In short, the stronger the professional competence, the higher the performance success achieved, because of the contribution of intellectual ability as an independent domain.